Particle swarm optimization based specified order robust-gap H∞ loop shaping controller design - Konghuayrob, Poom; Kaitwanividvilai, Somyot (My University, 2017)
The demand of data storage capacity in hard disk drive is expected to increase significantly which the areal density will achieve 10 Tbit/in2 in the near future. An increase of high areal density leads to the reduction of distance per data tracks. Due to the narrow track pitch, hard disk drive system is easily sensitive to the disturbance and noise. This is the benchmark problem for controlling the high precision servo mechanism. The alternative robust loop shaping based v-gap metric is proposed to synthesize the optimal controller for stabilizing a voice coil motor in hard disk drive servo system. Additionally, the designed loop shaping is evaluated by the Riccati procedure with regard to the system robustness. This paper applies the potential particle swarm optimization (PSO) to minimize the close loop gap between the loop shaping of the plant with weighting function and the plant with proposed controller. Moreover, the structure of proposed controller can be specified as the 2nd order controller which is uncomplicated to implement in the actual application. The simulation illustrates similar results in terms of the performance tracking and disturbance rejection of proposed controller against the H∞ loop shaping. Furthermore, the system stability index called stability margin with 0.434 emphasizes the robustness of the proposed controller.
Keywords: Hard disk drive; H∞ loop shaping; Particle swarm optimization; Robust control; V-gap metric